2018
DOI: 10.7759/cureus.3589
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Regression of Merkel Cell Carcinoma of the Male Breast with Ongoing Immune Response

Abstract: Merkel cell carcinoma (MCC) is a rare cutaneous neuroendocrine tumor arising predominantly on sun-exposed skin among the elderly. The most common location is the head and neck, followed by the extremities. MCCs are highly aggressive tumors and rarely undergo spontaneous regression. We report a case of MCC which presented as a painless breast lump in an elderly male where the tumor regressed spontaneously after a biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…A thorough search in PubMed was performed in order to find all cases of epithelial BC–SR published so far (December 2022). Twenty-nine reported cases were found [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The results of our literature search are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough search in PubMed was performed in order to find all cases of epithelial BC–SR published so far (December 2022). Twenty-nine reported cases were found [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The results of our literature search are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Although breast carcinoma is a common malignancy, cases of SR described in the literature are extremely rare [ 3 , 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Hundreds of tumor regressions published so far have been reviewed; however, to date, only twenty-nine cases of regressed epithelial breast cancer can be considered reliable [ 3 , 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. We noticed that most of the patients were female in a wide age range.…”
Section: Discussionmentioning
confidence: 99%
“…A relevant aspect in MCC pathology is tumor regression, a known phenomenon that occurs in some tumors, such as melanomas, but is rare in MCC with an estimated incidence betwen 1.5% -3%. 7,8 There are no known predictors of tumor regression, as its mechanism is not fully understood. The regression process is probably related to a T-cell immune reaction, linked to the activation of a response stimulated by surgical intervention and apoptosis.…”
Section: Case Discussionmentioning
confidence: 99%
“…In this sense, these findings raise the possible influence of the immune response mediated by T cells in the tumor regression process, leading to apoptosis and cell necrosis. 7,8 There are reports, including metastatic MCC that presented regression. Studies have shown that stage III MCC with unknown primary site had a more favorable prognosis than those with an identified primary site, which demonstrates an important role in the immune mechanism regarding the evolution of the disease, even with nodal dissemination.…”
Section: Case Discussionmentioning
confidence: 99%
“…The burned-out tumors represent tumors presenting SR followed by metastases[ 21 , 22 ]. With regard to NENs, SR of the tumor has been reported in Merkel cell carcinoma (MCC), bile duct NET, and both lung and gastric large-cell NECs[ 23 - 26 ]. Longo et al [ 27 ] reported a case of inguinal lymphadenopathy histologically corresponding to MCC.…”
Section: Discussionmentioning
confidence: 99%